All-solid-waste-based aerogel adsorbent material as well as preparation method and application thereof

By using solid waste such as fly ash and coal gangue to replace the silicone source, and combining the process of alkaline industrial solid waste and waste salt, a full-solid waste-based aerogel adsorbent is prepared, which solves the problem of relying on expensive raw materials and strong alkaline reagents in traditional technology, and achieves low-cost and efficient aerogel preparation and high-value utilization of solid waste.

CN119565558APending Publication Date: 2025-03-07NANJING INST OF ENVIRONMENTAL SCI MINIST OF ECOLOGY & ENVIRONMENT OF THE PEOPLES REPUBLIC OF CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411857570.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art relies on expensive silicone sources and strong alkaline chemical reagents in the preparation of aerogels, limiting the large-scale commercial production and application of aerogels.

Method used

Solid waste rich in SiO2 and Al2O3 is used to replace the silicone source with solid waste such as fly ash and coal gangue, and prepare all-solid waste-based aerogels through the mixing, calcining, acid extraction and other processes of alkaline industrial solid waste and waste salt, avoiding the use of alkaline chemical reagents such as sodium hydroxide.

Benefits of technology

The efficient preparation of all solid waste-based aerogel is achieved, the production cost is reduced, the high-value utilization of solid waste is improved, and the prepared adsorbent has good adsorption performance and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565558A_ABST
    Figure CN119565558A_ABST
Patent Text Reader

Abstract

The invention discloses an all-solid-waste-based aerogel adsorbent material and a preparation method and application thereof.According to the all-solid-waste-based aerogel adsorbent material, fly ash, coal gangue, steel slag and other bulk solid waste serve as main raw materials, proportioning is conducted according to the raw material composition of the solid waste, Si, Al and Na elements in multiple solid waste are fully utilized, it is avoided that traditional solid-waste-based aerogel uses NaOH, Na2CO3 and other alkaline chemical reagents, and the preparation method is simple and environmentally friendly; and high-value utilization of the solid waste is realized. The all-solid-waste-based aerogel prepared through sol-gel, surface hydrophobic modification and CO2 supercritical drying technologies has good adsorption performance on various VOCs, the preparation process of an adsorbent is mild and controllable and environmentally friendly, and a new scheme is provided for adsorption of VOCs in a complex industrial environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of aerogels and gas adsorption materials, and in particular relates to a fully solid waste-based aerogel adsorbent material and a preparation method and application thereof. Background Art

[0002] Aerogel is a porous three-dimensional nanomaterial with controllable structure and is the lowest density solid material known so far. Aerogel has the characteristics of extremely high specific surface area, low thermal conductivity, low density, etc. and has broad application prospects in the fields of heat insulation, sound insulation, adsorption, catalyst carrier, etc. Traditional SiO 2 Aerogel is prepared by sol-gel using organosilicon sources as raw materials, but most organosilicon sources are expensive, which limits the large-scale commercial production and application of aerogel.

[0003] Use fly ash and coal gangue as the representative of SiO-rich 2 and Al 2 O 3 The use of solid waste to replace organosilane as a raw material for aerogel has become a hot topic in recent years. The solid waste is mixed with alkaline chemical reagents such as sodium carbonate and sodium hydroxide, and then alkali-melted at high temperature, and then hydrochloric acid or sulfuric acid is used to extract SiO 2 and Al 2 O 3 , solid waste-based aerogels can be prepared through processes such as impurity removal, standing gelation, aging, and drying. In the preparation process of solid waste-based aerogels, strong alkaline chemical reagents are still used, which is not conducive to further reducing the cost of solid waste-based aerogel preparation. Summary of the invention

[0004] Purpose of the invention: The technical problem to be solved by the present invention is to address the deficiencies in the prior art and provide a method for using alkaline solid waste to replace chemical substances such as sodium hydroxide to prepare all-solid waste-based aerogel materials, and use them as adsorbents in the field of environmental governance to achieve high-value utilization of solid waste.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing an all-solid waste-based aerogel adsorbent material comprises the following steps: (1) Grinding fly ash or coal gangue with alkaline industrial solid waste and waste salt and mixing them to obtain a solid waste mixture; (2) using a tablet press to press the solid waste mixture obtained in step (1) into blocks under a certain pressure, then calcining at 700-900° C. for 1-4 hours, and naturally cooling to room temperature; (3) The calcined material is ground again, and then put into a hydrochloric acid aqueous solution, stirred thoroughly, and then filtered to obtain a filtrate, and then the filtrate is stirred continuously until the solution shows obvious wall adhesion, and then allowed to stand to gel; (4) The gel obtained in step (3) is sealed and aged, and then soaked and washed with deionized water and anhydrous ethanol in sequence to remove impurities in the gel and replace the deionized water. During the solvent replacement process, the gel is sealed and stored in an oven; (5) performing surface hydrophobic modification on the gel after solvent replacement in step (4) to obtain a hydrophobic gel; (6) After drying the gel with hydrophobic surface modification in step (5), a solid waste-based aerogel adsorbent material with a nanoporous network structure is obtained.

[0006] Specifically, in step (1), the alkaline industrial solid waste is at least one of steel slag, alkali slag and red mud; and the main component of the waste salt is sodium chloride and / or sodium carbonate.

[0007] Specifically, in step (1), the fly ash or coal gangue, alkaline industrial solid waste and waste salt are mixed according to a mass ratio of (5-10): (4-12): (0.2-2); each raw material is mechanically ground, and the particle size of the material after grinding is less than 100 mesh.

[0008] Specifically, in step (1), the tablet press pressure is controlled at 15 MPa-20 MPa.

[0009] Specifically, in step (2), the heating rate of the calcination is controlled at 10-15°C / min.

[0010] Specifically, in step (3), the concentration of the hydrochloric acid aqueous solution is 3 mol / L-6 mol / L, and the mass ratio of the calcined material to the hydrochloric acid aqueous solution is (1-2):(6-10); the stirring is performed by magnetic stirring or mechanical stirring.

[0011] Specifically, in step (4), the sealing aging is carried out in an oven with the temperature controlled at 40-60° C. for 20-36 hours.

[0012] Specifically, in step (4), deionized water 2-5 times the volume of the gel is used for soaking and washing each time, and the solution is replaced every 2-6 hours, and the deionized water is used for soaking and washing more than twice; anhydrous ethanol 2-5 times the volume of the gel is used for soaking and washing each time, and the solution is replaced every 10-14 hours, and the solution is soaked and washed more than twice.

[0013] Specifically, in step (5), the surface hydrophobic modification uses a mixed solution containing a surface modifier and ethanol, wherein the surface modifier is at least one of trimethylchlorosilane, methyltrimethoxysilane, hexamethyldiazosilane, and trimethylethoxysilane; the mass ratio of the surface modifier to anhydrous ethanol is 1:(6-10); the volume of the mixed solution is 2-3 times the volume of the gel, and the surface hydrophobic modification time is 6-24 hours.

[0014] Furthermore, the all-solid waste-based aerogel adsorbent material prepared by the above-mentioned preparation method is also within the protection scope of the present invention.

[0015] Furthermore, the present invention also claims to protect the use of the above-mentioned all-solid waste-based aerogel adsorbent material in the adsorption and treatment of VOCs.

[0016] The solid waste-based aerogel raw materials provided by the present invention are all taken from various solid wastes, and the prepared adsorbent has good adsorption performance and adsorption cycle stability. Beneficial Effects

[0017] (1) The all-solid waste-based aerogel adsorption material of the present invention can realize the high-value utilization of various solid wastes. It uses fly ash, coal gangue, steel slag and other bulk solid wastes as the main raw materials, utilizes the strong alkaline environment of industrial solid waste, and appropriately supplements waste salt to increase the Na ion content in the system. The NaAlSiO 4 、NaAlO 2 The strong acidic environment of acid leaching is further utilized to achieve efficient extraction of effective elements such as Si and Al, and the Si, Al and Na elements in various solid wastes are fully utilized. 2 All-solid waste-based aerogel adsorbent materials were prepared by supercritical drying.

[0018] (2) The present invention mixes the raw materials according to the composition of each solid waste, avoiding the use of NaOH, Na 2 CO 3 Alkaline chemical reagents such as sol-gel, surface hydrophobic modification and CO 2 The all-solid waste-based aerogel prepared by supercritical drying process has good adsorption performance for various VOCs. The adsorbent preparation process is mild, controllable and environmentally friendly, providing a new solution for the adsorption of VOCs in complex industrial environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0020] Figure 1 These are actual photos of the all-solid waste-based aerogel materials prepared in various embodiments.

[0021] Figure 2 Contact angle photos of all-solid waste-based aerogel materials prepared in various embodiments.

[0022] Figure 3 N is the total solid waste-based aerogel material prepared in each embodiment.2 Adsorption-desorption curve diagram.

[0023] Figure 4 This is a microscopic morphology of the all-solid waste-based aerogel material prepared in Example 1.

[0024] Figure 5 This is a relationship diagram between the saturated adsorption capacity of the all-solid waste-based aerogel material for n-hexane and the number of adsorption and desorption cycles in Example 1. DETAILED DESCRIPTION

[0025] The present invention can be better understood with reference to the following examples.

[0026] In the following examples, the fly ash comes from a power company in Shandong Province, and the main component of the fly ash is 31.2% Al 2 O 3 , 61.3% SiO 2 and 4.4% CaO.

[0027] The steel slag comes from a steel enterprise in Anhui Province. The main component of the steel slag is 6.9% Al 2 O 3 , 10.5% SiO 2 , 5.8% MgO, 44.6% CaO and 16.65% Fe 2 O 3 .

[0028] Red mud comes from an aluminum chemical company in Shandong. The main component of red mud is 25.6% Al 2 O 3 , 17.9% SiO 2 , 14.1% of Na 2 O, 0.7% CaO, 36.3% Fe 2 O 3 .

[0029] Waste salt comes from a chemical company in Tai'an. The main components of waste salt are 89.4% NaCl and 0.6% SiO 2 , 6.9% NaNO 3 . Example 1

[0030] A fully solid waste-based aerogel adsorbent material comprises the following steps: Step 1: Mechanically grind and mix fly ash, steel slag, red mud and waste salt in a mass ratio of 10:4:4:1; Step 2: The mixed material is pressed into a cuboid of about 5cm*5cm*3cm using a tablet press at a pressure of 18MPa, and then placed in a muffle furnace for calcination at a high temperature of 700°C for 3 hours, and then cooled naturally; Step 3: grind the calcined material mechanically to more than 100 mesh, use 5 mol / L hydrochloric acid to dissolve the material, the mass ratio of the material to hydrochloric acid is 1:8, stir thoroughly for 20 minutes and then filter, continue stirring until the solution is observed to have obvious wall adhesion and then stand to gel; Step 4: After sealing the gel, place it in an oven at 50°C for aging for 24 hours, soak the gel in deionized water 4 times the volume of the gel, replace the deionized water every 3 hours, and soak and wash 5 times, then soak the gel in anhydrous ethanol 4 times the volume of the gel, replace the anhydrous ethanol every 12 hours, and soak and wash 4 times. During the solvent replacement process, the gel is sealed and stored in an oven at 50°C. Step 5: The gel after solvent replacement is subjected to surface hydrophobic modification, wherein the surface modifier is a mixed solution of trimethylchlorosilane and anhydrous ethanol in a mass ratio of 1:8, and the volume of the surface modification mixed solution is 3 times the volume of the gel, and the gel is sealed and placed in a 50°C oven for surface modification for 24 hours; Step 6: Use CO 2 Supercritical drying to obtain a solid waste-based aerogel with a nanoporous network structure. The actual sample is shown in Figure 1 .

[0031] The hydrophobic angle of the prepared aerogel reached 141.64°. Figure 2 As shown. The specific surface area is 1043.84m 2 / g,N 2 The adsorption-desorption curves are shown in Figure 3 . Figure 4 This is a microscopic morphology of the all-solid waste-based aerogel material prepared in Example 1.

[0032] The saturated adsorption capacities of ethanol, hexane, isopropanol and dimethylformamide solutions are 11.29 g / g, 8.23 ​​g / g, 11.34 g / g and 14.62 g / g, respectively. Taking hexane as the adsorption object, after saturated adsorption at room temperature, it is desorbed in a 105 degree oven. After 10 cycles of adsorption and desorption, the saturated adsorption capacity retention rate is 88.51%. Figure 5 shown. Example 2

[0033] Step 1: Mechanically grind and mix fly ash, red mud and waste salt in a mass ratio of 10:10:1.2; Step 2: The mixed material is pressed into a cuboid of about 5cm*5cm*3cm using a tablet press at a pressure of 15MPa, and then placed in a muffle furnace for calcination at a high temperature of 750°C for 2.5 hours, and then cooled naturally; Step 3: Mechanically grind the calcined material to more than 100 mesh, use 4 mol / L hydrochloric acid to dissolve the material, the mass ratio of the material to hydrochloric acid is 1:10, fully stir for 20 minutes and then filter, continue stirring until the solution is observed to have obvious wall adhesion and then stand to gel; Step 4: After sealing the gel, place it in an oven at 50°C for aging for 24 hours, soak the gel in deionized water 5 times the volume of the gel, replace the deionized water every 4 hours, and soak and wash 6 times, then soak the gel in anhydrous ethanol 5 times the volume of the gel, replace the anhydrous ethanol every 12 hours, and soak and wash 4 times. During the solvent replacement process, the gel is sealed and stored in an oven at 50°C. Step 5: The gel after solvent replacement is subjected to surface hydrophobic modification, wherein the surface modifier is a mixed solution of trimethylchlorosilane and anhydrous ethanol in a mass ratio of 1:8, and the volume of the surface modification mixed solution is 3 times the volume of the gel, and the gel is sealed and placed in a 50° C. oven for surface modification for 24 hours; Step 6: Use CO 2 Supercritical drying to obtain a solid waste-based aerogel with a nanoporous network structure. The actual sample is shown in Figure 1 .

[0034] The hydrophobic angle of the prepared aerogel reached 137.1°. Figure 2 As shown. The specific surface area is 1073.67m 2 / g,N 2 The adsorption-desorption curves are shown in Figure 3 The saturated adsorption capacities of ethanol, hexane, isopropanol and dimethylformamide solutions are 12.19 g / g, 8.72 g / g, 14.37 g / g and 16.49 g / g, respectively. Taking hexane as the adsorption object, after saturated adsorption at room temperature, desorption was carried out in a 105 degree oven. After 10 cycles of adsorption and desorption, the saturated adsorption capacity retention rate was 82.64%. Figure 5 shown. Example 3

[0035] Step 1: Mechanically grind and mix the coal gangue, steel slag, red mud and waste salt in a mass ratio of 10:3:5:0.5; Step 2: The mixed material is pressed into a cuboid of about 5cm*5cm*3cm using a tablet press at a pressure of 20MPa, and then placed in a muffle furnace for calcination at a high temperature of 800°C for 2 hours, and then cooled naturally; Step 3: Mechanically grind the calcined material to more than 100 mesh, use 6 mol / L hydrochloric acid to dissolve the material, the mass ratio of the material to hydrochloric acid is 1:6, fully stir for 20 minutes and then filter, continue stirring until the solution is observed to have obvious wall adhesion and then stand to gel; Step 4: After sealing the gel, place it in an oven at 50°C for aging for 24 hours, soak the gel in deionized water 3 times the volume of the gel, replace the deionized water every 4 hours, and soak and wash 5 times, then soak the gel in anhydrous ethanol 5 times the volume of the gel, replace the anhydrous ethanol every 12 hours, and soak and wash 3 times. During the solvent replacement process, the gel is sealed and stored in an oven at 50°C. Step 5: The gel after solvent replacement is subjected to surface hydrophobic modification, wherein the surface modifier is a mixed solution of trimethylchlorosilane and anhydrous ethanol in a mass ratio of 1:8, and the volume of the surface modification mixed solution is 3 times the volume of the gel, and the gel is sealed and placed in a 50° C. oven for surface modification for 24 hours; Step 6: Use CO 2 Supercritical drying to obtain a solid waste-based aerogel with a nanoporous network structure. The actual sample is shown in Figure 1 .

[0036] The hydrophobic angle of the prepared aerogel reached 142.53°. Figure 2 As shown. The specific surface area is 923.18m 2 / g,N 2 The adsorption-desorption curves are shown in Figure 3 The saturated adsorption capacities of ethanol, n-hexane, isopropanol and dimethylformamide solutions are 10.81 g / g, 7.96 g / g, 12.49 g / g and 10.67 g / g, respectively. n-hexane is used as the adsorption object. After saturated adsorption at room temperature, it is desorbed in a 105 degree oven. After 10 cycles of adsorption and desorption, the saturated adsorption capacity retention rate is 91.23%. Figure 5 shown.

[0037] The present invention provides a solid waste-based aerogel adsorbent material and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a solid waste-based aerogel adsorbent material, characterized in that: The steps include: (1) Grinding fly ash or coal gangue with alkaline industrial solid waste and waste salt and mixing them to obtain a solid waste mixture; (2) calcining the solid waste mixture obtained in step (1) at 700-900° C. for 1-4 hours and naturally cooling to room temperature; (3) The calcined material is ground again, and then put into a hydrochloric acid aqueous solution, stirred thoroughly, and then filtered to obtain a filtrate, and then the filtrate is stirred continuously until the solution shows obvious wall adhesion, and then allowed to stand to gel; (4) The gel obtained in step (3) is sealed and aged, and then soaked and washed with deionized water and anhydrous ethanol in sequence to remove impurities in the gel and replace the deionized water. During the solvent replacement process, the gel is sealed and stored in an oven; (5) performing surface hydrophobic modification on the gel after solvent replacement in step (4) to obtain a hydrophobic gel; (6) After drying the gel with hydrophobic surface modification in step (5), a solid waste-based aerogel adsorbent material with a nanoporous network structure is obtained.

2. The method for preparing the all-solid waste-based aerogel adsorbent material according to claim 1, characterized in that: In step (1), the alkaline industrial solid waste is at least one of steel slag, alkali slag and red mud; and the main component of the waste salt is sodium chloride and / or sodium carbonate.

3. The method for preparing the all-solid waste-based aerogel adsorbent material according to claim 1, characterized in that: In step (1), the fly ash or coal gangue, alkaline industrial solid waste and waste salt are mixed according to a mass ratio of (5-10): (4-12): (0.2-2); each raw material is mechanically ground, and the particle size of the material after grinding is less than 100 mesh.

4. The method for preparing the all-solid waste-based aerogel adsorbent material according to claim 1, characterized in that: In step (2), the heating rate of the calcination is controlled at 10-15°C / min.

5. The method for preparing the all-solid waste-based aerogel adsorbent material according to claim 1, characterized in that: In step (3), the concentration of the hydrochloric acid aqueous solution is 3 mol / L-6 mol / L, and the mass ratio of the calcined material to the hydrochloric acid aqueous solution is (1-2):(6-10); the stirring is carried out by magnetic stirring or mechanical stirring.

6. The method for preparing the all-solid waste-based aerogel adsorbent material according to claim 1, characterized in that: In step (4), the sealing aging is carried out in an oven at a temperature controlled at 40-60° C. for 20-36 hours.

7. The method for preparing an all-solid waste-based aerogel adsorbent material according to claim 1, characterized in that: In step (4), 2-5 times the volume of the gel is used for soaking and washing each time, and the volume is changed every 2-6 hours, and the deionized water is used for soaking and washing more than twice; 2-5 times the volume of the gel is used for soaking and washing each time, and the volume is changed every 10-14 hours, and the anhydrous ethanol is used for soaking and washing more than twice.

8. The method for preparing an all-solid waste-based aerogel adsorbent material according to claim 1, characterized in that: In step (5), the surface hydrophobic modification uses a mixed solution containing a surface modifier and ethanol, wherein the surface modifier is at least one of trimethylchlorosilane, methyltrimethoxysilane, hexamethyldiazosilane, and trimethylethoxysilane; the mass ratio of the surface modifier to anhydrous ethanol is 1:(6-10); the volume of the mixed solution is 2-3 times the volume of the gel, and the surface hydrophobic modification time is 6-24 hours.

9. The all-solid waste-based aerogel adsorbent material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the all-solid waste-based aerogel adsorbent material according to claim 9 for adsorption and treatment of VOCs.

Citation Information

Cited By

  • Fly ash-based aerogel adsorption material and preparation method and application thereof

    CN122682549A